Application of systems thinking: 12‐month postintervention evaluation of a complex health system intervention in Zambia: the case of the BHOMA. Issue 2 (26th May 2015) - Mutale, Wilbroad; Ayles, Helen; Bond, Virginia; Chintu, Namwinga; Chilengi, Roma; Mwanamwenge, Margaret Tembo; Taylor, Angela; Spicer, Neil; Balabanova, Dina
Abstract: Rationale, aims and objectives: Strong health systems are said to be paramount to achieving effective and equitable health care. The World Health Organization has been advocating for using system‐wide approaches such as 'systems thinking' to guide intervention design and evaluation. In this paper we report the system‐wide effects of a complex health system intervention in Zambia known as Better Health Outcome through Mentorship and Assessment (BHOMA) that aimed to improve service quality. Methods: We conducted a qualitative study in three target districts. We used a systems thinking conceptual framework to guide the analysis focusing on intended and unintended consequences of the intervention. NVivo version 10 was used for data analysis. Results: The addressed community responded positively to the BHOMA intervention. The indications were that in the short term there was increased demand for services but the health worker capacity was not severely affected. This means that the prediction that service demand would increase with implementation of BHOMA was correct and the workload also increased, but the help of clinic lay supporters meant that some of the work of clinicians was transferred to these lay workers. However, from a systems perspective, unintended consequences also occurred during the implementation of the BHOMA. Conclusions: We applied an innovative approach to evaluate a complex intervention in low‐income settings, exploring empirically how systems thinking can be applied in the context of health system strengthening. Although the intervention had some positive outcomes by employing system‐wide approaches, we also noted unintended consequences.